SCN1A-related epilepsy with recessive inheritance: Two further families. (July 2021) - Moretti, Raffaella; Arnaud, Lionel; Bouteiller, Delphine; Trouillard, Oriane; Moreau, Patricia; Buratti, Julien; Rastetter, Agnès; Keren, Boris; Des Portes, Vincent; Toulouse, Joseph; Gourfinkel-An, Isabelle; Leguern, Eric; et al.
Abstract: Background: Variants in SCN1A gene, encoding the voltage-gated sodium channel Nav 1.1, are associated with distinct epilepsy syndromes ranging from the relatively benign genetic epilepsy with febrile seizures plus (GEFS+) to Dravet syndrome, a severe developmental and epileptic encephalopathy (DEE). Most SCN1A pathogenic variants are heterozygous changes inherited in a dominant or de novo inheritance and many cause a loss-of-function of one allele. To date, recessive inheritance has been suggested in only two families with affected children harboring homozygous SCN1A missense variants while their heterozygous parents were asymptomatic. The aim of this report is to describe two additional families in which affected individuals have biallelic SCN1A variants possibly explaining their phenotype. Methods and results: We report two novel homozygous SCN1A missense variants in two patients from related parents. Both patients had fever-sensitive epilepsy beginning in the first months of life, followed by afebrile seizures, without severe cognitive impairment. Parents were asymptomatic. Next generation sequencing excluded a pathogenic variant in other genes involved in DEE. Estimation of pathogenicity scores by in-silico tools suggests that the impact of these SCN1A variants is less damaging than that of dominant pathogenic variants. Conclusion: This study provides additional evidence that homozygous variants in SCN1A can cause GEFS+. This recessive inheritance would imply that hypomorphic variants may not necessarily cause epilepsy at the heterozygous state but may decrease the seizure threshold when combined. HIGHLIGHTS: SCN1A is the major gene involved in Dravet and GEFS+ syndromes. Almost all SCN1A pathogenic variants are heterozygous. To date, only two families with a homozygous inheritance of SCN1A variants have been reported. This study provides two additional cases of homozygous variants in SCN1A in patients with GEFS+. In silico prediction of variant pathogenicity are consistent with a milder effect on the protein, suggesting that variants could be tolerated at the heterozygous state but deleterious at the homozygous state.